Accounting Information Digitalization and Nigerian Firms’ Financial Performance - Adurayemi, Adu Cecilia; Olalekan, Majeobaje Ismail (International Journal of Sustainability in Research, 2024)
The study focused on the effect of digitalization of accounting information on firms’ financial performance in Nigeria. The study employed correlation matrix to determine the effect of information technology of accounting information on the financial performance of selected banking firms and least square regression to test the hypothesis using Statistical Package for Social Sciences (SPSS 20). From the analysis the study revealed that there is a significant relationship between Information technology on accounting system; there is a significant effect of large data in the function of accounting system, there is a significant impact of Artificial intelligence on how an organization processes its accounting information. The researcher therefore recommended that Digitalization of accounting information should be implemented in most firms as it reduces the weakness of loss of data. Accounting staffs should improve their capabilities in the use of digitalized accounting information systems and applied systems as it enables faster creation of financial report of business organizations in Nigeria.